2017
DOI: 10.1002/2017ja024317
|View full text |Cite
|
Sign up to set email alerts
|

Wave coupling from the lower to the middle thermosphere: Effects of mean winds and dissipation

Abstract: Recent observational and modeling evidence has demonstrated that planetary waves can modulate atmospheric tides, and secondary waves arising from their nonlinear interactions are an important source of both temporal and longitude variability in the thermosphere. While significant progress has been made on understanding how this form of vertical coupling occurs, uncertainty still exists on how the horizontal structures of primary and secondary waves evolve with height and the processes responsible for this evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 93 publications
12
44
0
Order By: Relevance
“…Note that the 90 day signals in CHAMP and GOCE DE3 (Figures a and b ) do not maximize exactly at the same time. This is likely due to “edge effects” in the GOCE wavelet (GOCE data starts on 1 November 2009), biases in the CHAMP and GOCE DE3 determinations (see discussion in section 2), and possible variations of this tidal components between ∼260 km and ∼330 km due to the effect of height‐dependent mean winds (see, e.g., Gasperini, ). Also note that because of the gaps and edge effects in GOCE data, the timing of the 90 day oscillation in GOCE mean wind and DE3 wavelets is heavily impacted by uncertainties in the data analysis (e.g., the peaks around days 400–480 may be caused by the fact that GOCE is missing the large signals before day 360).…”
Section: Resultsmentioning
confidence: 99%
“…Note that the 90 day signals in CHAMP and GOCE DE3 (Figures a and b ) do not maximize exactly at the same time. This is likely due to “edge effects” in the GOCE wavelet (GOCE data starts on 1 November 2009), biases in the CHAMP and GOCE DE3 determinations (see discussion in section 2), and possible variations of this tidal components between ∼260 km and ∼330 km due to the effect of height‐dependent mean winds (see, e.g., Gasperini, ). Also note that because of the gaps and edge effects in GOCE data, the timing of the 90 day oscillation in GOCE mean wind and DE3 wavelets is heavily impacted by uncertainties in the data analysis (e.g., the peaks around days 400–480 may be caused by the fact that GOCE is missing the large signals before day 360).…”
Section: Resultsmentioning
confidence: 99%
“…Numerical simulations (Palo et al, 1999) and observations (Moudden & Forbes, 2013) focused on the terrestrial atmosphere suggest that SWs propagate away from their sources as independent oscillations. Each SW is affected differently by the background wind field and dissipation (e.g., Gasperini, Forbes, & Hagan, 2017).…”
Section: Investigating Nonlinear Interactions Using Pseudolongitudesmentioning
confidence: 99%
“…The height-latitude structure of the UFKW and sidebands 2 − , 3 − , 1 + , 2 + between ±30 ∘ latitude and extending from 30 to 80 km retrieved using the pseudolongitude spectral peaks in MCS ZMR temperatures is presented in Figure 5. The UFKW is found to maximize around 78 km and possess amplitudes up to 6 K, while the sidebands are found to maximize around 70-75 km (2 − , 3 − ), 60-70 km (1 + ), and 68 km (2 + ) with amplitudes up to 4 K. The UFKW and the 2 − sideband are mostly equatorially symmetric, while the sidebands 3 − , 1 + , and 2 + display significant latitudinal asymmetry possibly due to tidal structures that are not purely symmetric (e.g., Moudden & Forbes, 2015) and/or to the effect of mean winds and dissipation (e.g., Gasperini, Forbes, & Hagan, 2017). Figure 5 also shows that the UFKW is mainly confined to a narrow latitude band of ±15 ∘ around of the equator, while the sidebands can extend up to ∼ ±30 ∘ latitude.…”
Section: Maven's Latitudinal Precession Is Such That Periapsis Is Withinmentioning
confidence: 99%
“…It should be borne in mind that migrating solar tides have a large zonal phase velocity (~400 m/s) near the equator that makes their linear interaction with the background winds unlikely; outside the tropics, their phase velocity decreases with the cosine of latitude, which results in important tidal amplitude modulations and seasonal asymmetries (Forbes & Vial , ; Forbes & Vincent, ). Moreover, intraseasonal variability of migrating tides due to zonal mean flow modulation is more likely to be mediated by nonlinear process, such as variations of the width of the tropical wave‐guide (McLandress, ), intraseasonal zonal wind asymmetries and dissipation rate (Gasperini et al, ), or other nonlinear processes. On the other hand, nonmigrating tides have vastly different zonal phase velocities, making their interactions with the background atmospheric wind in the lower atmosphere more likely.…”
Section: Intraseasonal Variabilitymentioning
confidence: 99%
“…Nonlinear wave‐wave interactions have been postulated for a long time to explain observed tidal variability in the upper atmosphere (e.g., Cevolani & Kingsley, ; Kamalabadi et al, ; Manson et al, ), but only in the last decade theoretical advances have revealed the complexity and variety of interactions that can occur in the upper atmosphere (Gasperini et al, ; Lieberman et al, , ; Pedatella et al, ); at the same time, numerical hindcasting simulations driven by data have indicated concurrence with the variability of the lower atmosphere (Sassi et al, ; Wang et al, ). A theoretical framework for such non‐linear interactions has been suggested by Teitelbaum and Vial (), who noted that while short‐term (approximately few hours) variations of tidal characteristic are likely associated with local (i.e., thermospheric) processes such as wave‐wave interactions, longer‐term (approximately few days or longer) variability may be instead associated with sources and/or propagation characteristics (see also Bernard, ).…”
Section: Intraseasonal Variabilitymentioning
confidence: 99%